"...4542 Miles from Home...": Repositioning English Language Learners as Power Brokers and Teachers as Learners in the Study Abroad Context - Kenneth J. Fasching-Varner; Michaela P. Stone; Roberto Mora Mella; Francisco Olave Henríquez; Macarena Yacoman Palma (MDPI AG, 2019)
This article provides an empirical context for the role that bi/multi-lingual children and families may play in supporting pre-service and in-service educators engaging difference through a literacy and language situated study abroad internship in Chile. Drawing on data over a 15-year longitudinal study of the program, the authors examine how students and parents navigate serving the role of teacher, whereas the teacher participants navigate a new role as a learner in a context where they, many for the first time, experience being language and cultural minorities.